Marketing promocional en la difusión del aceite medicinal cáñamo en la ciudad de Guayaquil 2022 – 2023 - Heredia Marín, Freddy Javier (2023)
In the Ecuadorian population there are a series of inflammatory conditions, for example, different types of cancer, long bone fractures, Parkinson's disease. For your care there are a series of products on the market, mainly of chemical origin, however, this type of medication usually causes side effects that can be worse in some cases than the disease itself, which is why the use of Hemp for medicinal use as an alternative. Considering this context, the objective is to establish promotional marketing strategies for the introduction of hemp medicinal oil in the city of Guayaquil. For this, a non-experimental design was used that was applied cross-sectionally, the inductive method was used specifically for the study and analysis of the data collected from the surveys, the research approach was quantitative. The technique used to collect information was the survey. The population chosen for this research is made up of all the people who are dedicated to the purchase of hemp-based medicinal oils in the city of Guayaquil. After completing the study, it was concluded that the main knowledge that potential customers have in relation to hemp oil is: excellent quality, in turn they are attracted by the price of the product and its quality, or efforts are made of marketing that allow arousing interest in the hemp oil that is offered to the potential market.